1998
DOI: 10.1590/s0034-71081998000400010
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade dos parasitóides Spilochalcis morleyi (Hymenoptera, Chalcididae) e Xanthozona melanopyga (Diptera, Tachinidae) em pupas femininas e masculinas de Brassolis sophorae (Lepidoptera, Nymphalidae)

Abstract: Comparou-se o número médio de adultos emergidos, número de imaturos mortos e a freqüência com que ocorre a morte de toda a prole nos parasitóides Spilochalcis morleyi (Hymenoptera, Chalcididae) e Xanthozona melanopyga no hospedeiro, Brassolis sophorae (Lepidoptera, Nymphalidae). O número de parasitóides (Spilochalcis) que completaram seu desenvolvimento e emergiram foi significativamente maior em pupas femininas do hospedeiro. O número médio de imaturos de Spilochalcis mortos por pupa não diferiu entre os sexo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Among the parasitized pupae, one pupa alone produced 146 parasitoid (73 males and 73 females, therefore with a sexual proportion of one male for one female). The gregarious developmental behavior was also reported by Ruszczyk & Ribeiro (1998) in natural parasitism of B. sophorae pupae (females and males) by Spilochalcis morleyi Ashmead (valid name C. morleyi). These authors concluded that this parasitoid species seems to fit the number of descendants to the host size.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Among the parasitized pupae, one pupa alone produced 146 parasitoid (73 males and 73 females, therefore with a sexual proportion of one male for one female). The gregarious developmental behavior was also reported by Ruszczyk & Ribeiro (1998) in natural parasitism of B. sophorae pupae (females and males) by Spilochalcis morleyi Ashmead (valid name C. morleyi). These authors concluded that this parasitoid species seems to fit the number of descendants to the host size.…”
supporting
confidence: 55%
“…morleyi was recordered for Central and South America ( The list of its hosts is restricted, including two genus of Brassolinae: Brassolis -B. sophorae and B. astyra-and Opsiphanes -Opsiphanes sp. and O. invirae (Herting 1976, Ruszczyk & Ribeiro 1998. There is only a single record of plant associates: Cocos nucifera L. (Delvare 1992).…”
mentioning
confidence: 99%
“…Piracicaba, Campinas) (Travassos Filho & Carrera 1941, Costa Lima 1950, Mariconi & Zamith 1954, Silva et al 1968, Guimarães 1971, Guimarães 1977 Species of Diptera (Tachinidae and Sarcophagidae) (Ferreira & Lins 2002, Ruszczyk & Ribeiro 1998 have been recorded as pupal or larvipupal endoparasitoids, acting therefore as biological control agents of Brassolis sophorae (L.), a pest in coconut crops (Ferreira et al 1998). The present note reporter Xanthozona melanopyga (Wiedmann, 1830) parasitizing pupae of Brassolis astyra Godart, 1824, for the State of Rio Grande do Sul, Brazil.…”
mentioning
confidence: 99%
“…KEY WORDS: Natural enemy, Cocos nucifera, distribution, Alagoas, biocontrol Species of Hymenoptera (especially members of Chalcididae) and Diptera (Tachinidae and Sarcophagidae) (Ferreira & Lins 2002, Ruszczyk & Ribeiro 1998 have been recorded as pupal or larvipupal endoparasitoids, acting therefore as biocontrol agents of Brassolis sophorae (L.), a pest in coconut crops (Ferreira et al 1998). The present study records Winthemia analis (Macquart) (Fig 1A, B) parasitizing pupae of B. sophorae laurentii Stichel, in the State of Alagoas, Brazil.…”
mentioning
confidence: 99%
“…The examined parasitoid material was deposited at the Museu de Zoologia ( (Tachinini) (Piza & Zamith 1944) and Winthemia pinguis (Fabricius) (Exoristinae: Winthemiini) (Ruszczyk & Ribeiro 1998). Only W. pinguis was previously recorded and associated to a host species (on B. sophorae), among the South American species of Winthemia (Guimarães 1977).…”
mentioning
confidence: 99%